An Empirical Approach to Teaching Reading Comprehension (International Journal of Food and Nutritional Sciences, 2019)
Reading as a Process of Recognition and Interpretation: Reading involves the recognitionand interpretation of written or printed material. It encompasses the identification of letters,words, phrases, and clauses.